The Moulding of Ukraine - Kataryna Wolczuk (Central European University Press, 2001)
With the disintegration of the Soviet Union, a number of new states were created that had little or no claim to any previous existence. Ukraine is one of the countries that faced not only political, social and economic transformation, but also state formation and the redefinition of national identity. This book uses Ukraine as a case study in trying to trace the key moments of decision making in the course of creating a new state while shedding the legacies of ""Soviet-type"" statehood. The Mo...